Integration of the Thuma'ninah Concept in the Elementary Education Curriculum in the 21st Century Digital Era as an Antithesis to the Popcorn Brain Phenomenon within Digital Generation Narratives - Munisa Munisa; Sri Maryati; Basir Jarah Anilon; Sri Ratu Ratna Intan; Linda Ardiya Waroka (International Journal of Educational Narratives, 2026)
Background. Rapid technological development has significantly reshaped elementary students' learning habits, increasing their exposure to instant digital stimuli. Recent educational and psychological studies have highlighted growing concerns that excessive digital engagement contributes to shorter attention spans, impulsive thinking, emotional dysregulation, and dependence on immediate gratification. These trends threaten students' capacity for deep learning, reflective thinking, and character development, making it urgent to identify educational approaches that foster emotional balance and sustained attention. Purpose. This study aims to analyze the integration of the concept of thuma'ninah as a spiritual value into the elementary education curriculum as an alternative response to the popcorn brain phenomenon, contributing to the development of character-based education that enhances students' emotional stability, self-regulation, and learning engagement in the digital era. Method. This study employed a qualitative research design using a literature review approach. Data were collected and analyzed from relevant scientific publications in the fields of Islamic education, educational psychology, curriculum studies, and digital technology's influence on child development. Results. The review demonstrates that thuma'ninah, characterized by inner peace, reflective awareness, emotional stability, and self-control, can be systematically integrated into elementary education through the reinforcement of worship practices, structured reflective learning activities, and Islamic mindfulness-based instructional strategies. Consistent with previous studies on mindfulness and social-emotional learning, these approaches contribute to improved concentration, emotional regulation, learning engagement, and resilience against the negative cognitive effects associated with excessive digital stimulation. Conclusion. The integration of the concept of thuma'ninah into the elementary education curriculum represents a relevant and effective strategy for addressing the challenges posed by the popcorn brain phenomenon. It not only supports students' cognitive focus and emotional well-being but also contributes to developing morally grounded, reflective, and digitally resilient learners.